2019
DOI: 10.1021/acscentsci.9b00560
|View full text |Cite
|
Sign up to set email alerts
|

Self-Assembled Copolymer Adsorption Layer-Induced Block Copolymer Nanostructures in Thin Films

Abstract: In polymer thin films, the bottom polymer chains are irreversibly adsorbed onto the substrates creating an ultrathin layer. Although this thin layer (only a few nanometers thick) governs all film properties, an understanding of this adsorbed layer remains elusive, and thus, its effective control has yet to be achieved, particularly in block copolymer (BCP) thin films. Herein, we employ self-assembled copolymer adsorption layers (SCALs), transferred from the air/water interfacial self-assembly of BCPs, as an ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 59 publications
1
12
0
Order By: Relevance
“…As shown in the rest steps of Figure a, BCP nanopatterning is applied directly onto a PNM-coated substrate without an additional process. It should be noted that the physisorption of a PNM coating is irreversible and sufficiently stable to maintain their PNM patterns under severe experimental conditions such as spin-coating and thermal annealing, as reported in our previous study, and as discussed in a later section.…”
Section: Resultssupporting
confidence: 61%
“…As shown in the rest steps of Figure a, BCP nanopatterning is applied directly onto a PNM-coated substrate without an additional process. It should be noted that the physisorption of a PNM coating is irreversible and sufficiently stable to maintain their PNM patterns under severe experimental conditions such as spin-coating and thermal annealing, as reported in our previous study, and as discussed in a later section.…”
Section: Resultssupporting
confidence: 61%
“…This anisotropic roughness-induced alignment of BCP nanopatterns can be rationalized with a description of the system free energy. 18 The self-assembly of BCP thin films is sensitive to the interfacial conditions such as the BCP− substrate interface interactions 25,26 and a substrate roughness 27 in this study. The microphase separation of BCPs generally occurs toward the minimization of interface energy between BCP domains, 28 while the roughness of substrates increases the domain interfaces in BCP thin films.…”
Section: T H Imentioning
confidence: 74%
“…In our previous research, we reported that the ISA of BCPs can be applied as a self‐assembled copolymer adsorption layer (SCAL) in BCP thin films. [ 8 ] We found that the ISA of BCPs is irreversibly adsorbed on solid substrates to replace an inherent adsorption layer in BCP thin films when other BCPs are additionally coated on it. The replaced adsorption layer, SCAL, affects the self‐assembly of overlying BCPs.…”
Section: Resultsmentioning
confidence: 99%
“…[21] Furthermore, it has been known that the 2D chain conformation of hydrophilic P2VP chains could have maximized pining sites on the solid substrate, thus forming irreversible adsorption on the substrate with superior www.advmatinterfaces.de stability. [8] Due to this superior stability of irreversibly adsorbed nanostrand array, the additional spin-coating of BCPs is available without disturbing the ISA of BCP. Therefore, after the additional spin-coating of the BCPs on the BCP nanostrand layer, they replaced the inherent adsorption layer and affected to the self-assembly of overlying BCPs.…”
Section: Density-doubled Metal Nanowires and Hierarchical Bcp Self-as...mentioning
confidence: 99%
See 1 more Smart Citation